Prática do enfermeiro do Programa Saúde da Família PSF na promoção da saúde do adolescente - Nóbrega, Líbne Lidianne da Rocha e (2008)
Attention to the health of adolescents, based on paradigm flexneriano, needs to be overcome. Since the International Conference of Ottawa (1986), the literature is developing a discussion of the promotion of health, based on the paradigm of social production in health, suggests a design to overcome the health care traditional practices. Program Health of the Family PSF has this purpose to transmute the model of existing assistance, where the nurse is an essential element to the work done in the program. Around this context, it is our purpose to analyze the practice of nurse of the PSF for the promotion of health of adolescents, produced by a search of descriptive quantitative approach with the inclusion of qualitative data. Interviews were conducted with 9 nurses 3 units of health of the family USF, Mossoró-RN and applied questionnaires with 74 teenagers aged between 15 and 19 years old, with some nearby public schools where USF operate these nurses. The quantitative descriptions were transformed on tables, pictures and graphics using the program Excel (Microsoft) and the qualitative were worked through the technique of analyzing the content of Bardin (2004). The review was realized using the reference to promote health brought by the study. The results show that the most common problems that happen with teenagers are the drugs (33,8%), pregnancy (27,0%) and political problems-socio-economic-cultural issues (24,3%). Adolescents are spontaneous demand and rarely seek the USF. The actions presented by the nurses as, lectures and groups, are nothing comparing to the macro-problems presented by adolescents, and verticalized irregular. The nurses know the promotion of health generally, not explaining how operate it from its daily practice. Concluded that the practice of nurse of the PSF has not yet reach the promotion of health of the adolescent, being necessary to scheduling modules on the subject to continuous training of teams, professionals from USF, as well as teachers and other staff of schools, giving space to the participation of academic. The discussions should be socialized with the community to discuss possibilities of confrontation of the problems, which also require socio-structural changes. This research can contribute as work-diagnosis, which experienced the reality of care in nursing PSF to a specific group